Oxidant concentration effects in the hydroxylation of phenol over titanium-based zeolites Al-free Ti-Beta and TS-1 - Burton, Robert M (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2006.